Isotonic contraction as a result of cooperation of sarcomeres--a model and simulation outcome - Wünsch, Z (Bio Systems, 1996)
The molecular level of the functional structure of the contractile apparatus of cross-striated muscle has been mapped out almost minutely. Most authors accept the basic principles of the theory of sliding filaments and the theory of operation of molecular generators of force which, of course, are progressively updated by integrating new knowledge. The idea of the model delineated below does not contradict these theories, for it refers to another level of the system's hierarchy. The definition of the system, hereafter referred to Ideal Sarcomere (IS), takes into account the fact that, during isotonic contraction, a large number of not wholly independently working sarcomeres and molecular generators of force is active in a synergistic way. The shortening velocity of isotonically contracting IS is determined by the relation between quantities conveying different tasks of active generators of force and the influence of the system parameters. Although IS is derived from simple axiomatic predicates, it has properties which were not premediated in defining the system and which, in spite of this, correspond to some properties of the biological original. The equations of the system allow us to calculate the shortening velocity of 'isotonic contraction' and other variables and parameters and show, inter alia, an alternative way to derive and interpret the relations stated in Hill's force-velocity equation. The simulation results indicate that the macroscopic manifestations of isotonic contraction may be also contingent on the properties of the cooperating system of the multitude of sarcomeres, which also constitutes one part of the functional structure of muscle.
Keywords: biofyzikální jevy; Biophysics; počítačová simulace; termoregulace; Biophysical Phenomena; Humans; lidé; sarkomery; isotonická kontrakce; Sarcomeres; Models, Biological; techniky in vitro; biologické modely; biofyzika; Animals; Body Temperature Regulation; zvířata; In Vitro Techniques; Isotonic Contraction; Biomechanical Phenomena; biomechanika; Computer Simulation